Achieving the Millennium Development Goal of reducing maternal mortality in rural Africa: an experience from Burundi. Issue 2 (20th November 2012) - Tayler‐Smith, K.; Zachariah, R.; Manzi, M.; Van den, W.; Nyandwi, G.; Reid, T.; Van den, R.; De, E.; Lambert, V.; Nicolai, M.; Goetghebuer, S.; Christaens, B.; et al.
Abstract Objectives To estimate the reduction in maternal mortality associated with the emergency obstetric care provided by Médecins Sans Frontières (MSF) and to compare this to the fifth Millennium Development Goal of reducing maternal mortality. Methods The impact of MSF's intervention was approximated by estimating how many deaths were averted among women transferred to and treated at MSF's emergency obstetric care facility in Kabezi, Burundi, with a severe acute maternal morbidity. Using this estimate, the resulting theoretical maternal mortality ratio in Kabezi was calculated and compared to the Millennium Development Goal for Burundi. Results In 2011, 1385 women from Kabezi were transferred to the MSF facility, of whom 55% had a severe acute maternal morbidity. We estimated that the MSF intervention averted 74% (range 55–99%) of maternal deaths in Kabezi district, equating to a district maternal mortality rate of 208 (range 8–360) deaths/100 000 live births. This lies very near to the 2015 MDG 5 target for Burundi (285 deaths/100 000 live births). Conclusion Provision of quality emergency obstetric care combined with a functional patient transfer system can be associated with a rapid and substantial reduction in maternal mortality, and may thus be a possible way to achieve Millennium Development Goal 5 in rural Africa.